CHALLENGES AND PROSPECTS IN THE IMPLEMENTATION OF NEO-HUMANISTIC EDUCATION IN ELEMENTARY CLASSROOMS - Mantra, Ida Bagus Nyoman; Gede Bambang Erawan, Dewa; Kadek Sunastri, Ni; Wayan Sukardi, Ni (International Journal of Multidisciplinary Reseach, 2025)
Neo-humanistic education promotes universal empathy, holistic development, ecological consciousness, and the spiritual growth of learners. As educational paradigms evolve towards more inclusive and value-oriented methodologies, the importance of neo-humanistic education escalates, particularly at the basic level. This study investigates the obstacles and opportunities teachers and administrators face in implementing neo-humanistic pedagogy in primary classes. This study utilises a qualitative case study methodology to evaluate teacher interviews, classroom observations, and an analysis of educational policy texts. The findings highlight multiple structural, pedagogical, and cultural challenges and significant potential to improve students' empathy, environmental stewardship, and comprehensive learning. The research clarifies the effective incorporation of neo-humanistic education into traditional elementary schools.